2022
DOI: 10.1080/21655979.2022.2065789
|View full text |Cite
|
Sign up to set email alerts
|

Livogrit Prevents Methionine-Cystine Deficiency Induced Nonalcoholic Steatohepatitis by Modulation of Steatosis and Oxidative Stress in Human Hepatocyte-Derived Spheroid and in Primary Rat Hepatocytes

Abstract: The prevalence of nonalcoholic steatohepatitis (NASH), characterized by fatty liver, oxidative injury, and inflammation, has considerably increased in the recent years. Due to the complexity of NASH pathogenesis, compounds which can target different mechanisms and stages of NASH development are required. A robust screening model with translational capability is also required to develop therapies targeting NASH. In this study, we used HepG2 spheroids and rat primary hepatocytes to evaluate the potency of Livogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…According to bioinformatics analysis, CXCL2 is one of the key genes associated with NASH [ 81 ]. CXCL5 expression elevated in NASH cells and can be inhibited via Livogrit to alleviate the progression of NASH [ 82 ]. CXCL10 also takes a crucial part in NASH.…”
Section: Cxcl Family and Diseasesmentioning
confidence: 99%
“…According to bioinformatics analysis, CXCL2 is one of the key genes associated with NASH [ 81 ]. CXCL5 expression elevated in NASH cells and can be inhibited via Livogrit to alleviate the progression of NASH [ 82 ]. CXCL10 also takes a crucial part in NASH.…”
Section: Cxcl Family and Diseasesmentioning
confidence: 99%
“…Livogrit, a tri-herbal Ayurvedic medicine, was studied for its hepatoprotective effect on methionine and cysteine deficient NASH models in both HepG2 spheroids and rat primary hepatocytes. It reduced fat accumulation and ROS production and increased lipolysis hence attenuating NASH (Balkrishna et al, 2022) NAFLD is characterized by the accumulation of lipid droplets (LDs) in the hepatocytes, referred to as hepatic steatosis. It is considered as the "first-hit" in the development of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…In order to decipher the mode of action of Lipidom we evaluated the gene expression of OxLDL induced THP1 macrophages and found that Lipidom acts on the pathways responsible for inflammation (TNFα, MCP-1), lipid accumulation (FAS, ABCG1, FGF-21) and oxidative stress (Nrf2) [24][25][26]. It was found that Lipidom was able to normalize the expression of these genes by a multifaceted mode of action.…”
Section: Discussionmentioning
confidence: 99%